2019
DOI: 10.1021/acsaem.9b01173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concentrated Diglyme-Based Electrolytes on the Electrochemical Performance of Potassium-Ion Batteries

Abstract: The effect of salt concentration in diglyme-based electrolytes on cycling performance of promising KVOPO 4 and K 1.69 Mn[Fe(CN) 6 ] 0.85 •0.4H 2 O positive electrodes (cathodes) and a hard carbon negative electrode (anode) for next-generation potassium-ion (K-ion) batteries is investigated. A decrease in free solvent molecule number with increasing electrolyte concentration is found, which results in a better aluminum current collector stability, formation of thinner solid electrolyte interface (SEI) passivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 52 publications
0
42
0
Order By: Relevance
“…Alkali ion batteries (AIB) based on Li + , and emerging technologies based on K + , are important high-performance rechargeable energy storage devices. [1][2][3] Considerable recent efforts have been devoted to the fabrication of new electrode materials, 4 discovery of energy storage mechanisms, 5 electrochemical reactions at electrodes and interphases, 6,7 and towards improving the cell capacity, stability, and cyclability. 8 Upon AIB cycling, alkali ions are reversibly stored within both anode and cathode in the battery.…”
Section: Introductionmentioning
confidence: 99%
“…Alkali ion batteries (AIB) based on Li + , and emerging technologies based on K + , are important high-performance rechargeable energy storage devices. [1][2][3] Considerable recent efforts have been devoted to the fabrication of new electrode materials, 4 discovery of energy storage mechanisms, 5 electrochemical reactions at electrodes and interphases, 6,7 and towards improving the cell capacity, stability, and cyclability. 8 Upon AIB cycling, alkali ions are reversibly stored within both anode and cathode in the battery.…”
Section: Introductionmentioning
confidence: 99%
“…Sun's group optimized the concentration of ether‐based electrolyte and found that the high concentration ether‐based electrolyte could effectively stabilize the cycling performance of Bi@C electrode for KIBs . Also, Stevenson's group explored the effect of different concentration ether‐based electrolyte and found that high concentration ether‐based electrolyte could decrease the free solvent molecule, which would restrain the solvent degradation upon cycling . In spite of these works, more material systems cooperated with high concentration ether‐based still need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Li's group employed porous Bi combined with ether-based electrolyte for KIBs, delivering a superior reversible capacity and long cycle life. [30] In spite of these works, more material systems cooperated with high concentration ether-based still need to be explored. [28] Meanwhile, some works involving high concentration ether-based electrolyte have also received attention.…”
mentioning
confidence: 99%
“…Furthermore, reports by Mai et al [178] . and Stevenson et al [179] . also confirmed the unique contribution of ether‐based electrolytes in improving and optimizing the performance of PIBs.…”
Section: Electrolytesmentioning
confidence: 67%